2014
DOI: 10.1007/s00535-014-1031-2
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of gastric acid secretion over a 20-year period in normal Japanese men

Abstract: Considering that gastric acid secretion remained unchanged in H. pylori-negative Japanese men over a 20-year period at a level much lower than that in Occidental subjects, upper gastrointestinal disease profiles in the Japanese population will differ from those in Western countries in the post-H. pylori era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
0
29
1
Order By: Relevance
“…This finding contrasts with our recent report in which gastric acid secretion did not change during the same period in H. pylori-negative asymptomatic outpatients with a mean age of 63 years (Iijima et al 2015). Moreover, in that study, an additional subgroup analysis in 47 H. pylori-negative outpatients over the age of 65 reveals that there is no change in gastric acid secretion between 1995 and 2014 (r = 0.03, p = 0.83).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This finding contrasts with our recent report in which gastric acid secretion did not change during the same period in H. pylori-negative asymptomatic outpatients with a mean age of 63 years (Iijima et al 2015). Moreover, in that study, an additional subgroup analysis in 47 H. pylori-negative outpatients over the age of 65 reveals that there is no change in gastric acid secretion between 1995 and 2014 (r = 0.03, p = 0.83).…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, we applied the same definition of the chronological periods as in our preceding study (Iijima et al 2015) so as to help compare the difference between the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in the 1990 s of Japanese subjects showed that gastric acid secretion levels increased from the 1970 s to 1990 s, though they remained lower as compared to Europeans and North Americans 19 20 21. In addition, those levels have not increased over the past 2 decades in Japanese 22 23. These factors may be related to the lower prevalence of GERD in Asian individuals as compared to Western populations.…”
Section: Discussionmentioning
confidence: 93%